A Review of The Models of Land Development Process: The Agency Models - Ismail, Maziah (Fakulti Ukur dan Harta Tanah, 1996)
In paper 1 it was revealed that both the equilibrium and event-sequence models of the land development process lack emphasis on the relationship of agents involved where the actors are treated as homogenous, with equal freedom of entry and having perfect knowledge of the market. In tms paper 2, the agency model suggested that, in reality, the actors are heterogenous, monopoly powers dominate and knowledge is imperfect. However, it is concluded .that this model gives too much emphasis to the actors and the interactions. Hence, it is too descriptive and lacking critical appraisal as well as mention of the wider forces.